Retracing our steps to understand ketamine in depression: A focused review of hypothesized mechanisms of action - Madison N. Irwin, PharmD; Amy VandenBerg, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2021)
Introduction: MDD represents a significant burden worldwide, and while a number of approved treatments exist, there are high rates of treatment resistance and refractoriness. Ketamine, an N-methyl-d-aspartate receptor (NMDAR) antagonist, is a novel, rapid-acting antidepressant, however the mechanisms underlying the efficacy of ketamine are not well understood and many other mechanisms outside of NMDAR antagonism have been postulated based on preclinical data. This focused review aims to present a summary of the proposed mechanisms of action by which ketamine functions in depressive disorders supported by preclinical data and clinical studies in humans. Methods: A literature search was completed using the PubMed and Google Scholar databases. Results were limited to clinical trials and case studies in humans that were published in English. The findings were used to compile this article. Results: The antidepressant effects associated with ketamine are mediated via a complex interplay of mechanisms; key steps include NMDAR blockade on ?-aminobutyric acid interneurons, glutamate surge, and subsequent activation and upregulation of ?-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor. Discussion: Coadministration of ketamine for MDD with other psychotropic agents, for example benzodiazepines, may attenuate antidepressant effects. Limited evidence exists for these effects and should be evaluated on a case-by-case basis.